Preparation, Properties, and Self-Assembly Behavior of PTFE-Based Core-Shell Nanospheres. (29th February 2012) - Sparnacci, Katia; Antonioli, Diego; Deregibus, Simone; Laus, Michele; Zuccheri, Giampaolo; Boarino, Luca; De Leo, Natascia; Comoretto, Davide
Abstract : Nanosized PTFE-based core-shell particles can be prepared by emulsifier-free seed emulsion polymerization technique starting from spherical or rod-like PTFE seeds of different size. The shell can be constituted by the relatively high Tg polystyrene and polymethylmethacrylate as well as by low Tg polyacrylic copolymers. Peculiar thermal behavior of the PTFE component is observed due to the high degree of PTFE compartmentalization. A very precise control over the particle size can be exerted by properly adjusting the ratio between the monomers and the PTFE seed. In addition, the particle size distribution self-sharpens as the ratio monomer/PTFE increases. Samples with uniformity ratios suited to build 2D and 3D colloidal crystals are easily prepared. In particular, 2D colloidal crystal of spheres leads to very small 2D nanostructuration, useful for the preparation of masks with a combination of nanosphere lithography and reactive ion etching. 3D colloidal crystals were also obtained featuring excellent opal quality, which is a direct consequence of the monodispersity of colloids used for their growth.